1988
DOI: 10.1073/pnas.85.3.684
|View full text |Cite
|
Sign up to set email alerts
|

Complex between carboxypeptidase A and a hydrated ketomethylene substrate analogue.

Abstract: The complex of carboxypeptidase A (CPA) with 5-amino-(N-t-butoxycarbonyl)-2-benzyl-4-oxo-6-phenylhexanoic acid (BBP), the ketomethylene substrate analogue of the peptide substrate N-(t-butoxycarbonyl)-L-phenylalanyl-Lphenylalanine, was studied by x-ray crystallographic methods. Interestingly, the enzyme specifically binds only one of four stereoisomers of BBP that were present in the buffer solution in which the CPA crystals were soaked. Furthermore, the species observed to bind to the enzyme is the hydrated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Most likely the conformational flexibility of these residues is related to the two states of the active site; the free state and that with the substrate bound. Comparison of the present CPT structure with those of native CPA (Rees et al, 1983) and of CPA complexes (Rees et al, 1981 ;Shoham et al, 1988;Kim and Lipscomb, 1990;Kim and Lipscomb, 1991) suggests that the active site in CPT resembles the 'bound' state. Although the conformational changes observcd for Argl27 and Arg145 are not so pronounced as for Tyr248, they are clear enough to be described as changes in the hydrogenbonding network (here and in the following paragraph, the CPA numbering is used).…”
Section: T M P N G F a F T H S E --N R L W R K T R S V T S S S L C V mentioning
confidence: 97%
“…Most likely the conformational flexibility of these residues is related to the two states of the active site; the free state and that with the substrate bound. Comparison of the present CPT structure with those of native CPA (Rees et al, 1983) and of CPA complexes (Rees et al, 1981 ;Shoham et al, 1988;Kim and Lipscomb, 1990;Kim and Lipscomb, 1991) suggests that the active site in CPT resembles the 'bound' state. Although the conformational changes observcd for Argl27 and Arg145 are not so pronounced as for Tyr248, they are clear enough to be described as changes in the hydrogenbonding network (here and in the following paragraph, the CPA numbering is used).…”
Section: T M P N G F a F T H S E --N R L W R K T R S V T S S S L C V mentioning
confidence: 97%
“…CPA was purchased from Sigma Co.; the protein was further puri®ed and crystallized according to previously described procedures (Shoham et al, 1984(Shoham et al, , 1988. The fully grown crystals of native CPA were cross-linked prior to X-ray data measurement in order to impart greater mechanical strength.…”
Section: Crystallization and Data Collectionmentioning
confidence: 99%
“…CPA has been the subject of extensive research in the last 30 years (Coleman & Vallee, 1961;Neurath et al, 1970;Shoham et al, 1984Shoham et al, , 1988Christianson & Lipscomb, 1989;Feinberg et al, 1993Feinberg et al, , 1995Greenblatt et al, 1998). However, the exact catalytic mode of action of this representative enzyme and the rest of the zinc proteinase family is still not completely clari®ed.…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that the two tetrahedral oxygens of the gem-diol are stabilized by their interactions with the active site. That is, the gem-diol state is highly unstable in solution, unless strong electron attractors are present near the carbonyl 50. It was concluded that the gem-diol forms only as a result of interaction with the enzyme, while none could be detected in solution with no enzyme present 50.…”
Section: Introductionmentioning
confidence: 99%